Agreement between pre-exercise screening questionnaires completed online versus face-to-face. - Lynda Norton; Jessica Thomas; Nadia Bevan; Kevin Norton (PLoS ONE)
Objectives To investigate the levels of agreement between self-reported responses to the Adult Pre-exercise Screening System (APSS) questionnaire using online versus face-to-face (F2F) modalities. Design Convenience sample of adults completing a pre-exercise screening questionnaire using different modalities. Methods Adult volunteers (n = 94) were recruited to complete the APSS using both online and F2F modalities. Participants were provided a URL link to an online APSS questionnaire then followed-up the next day in a F2F interview. Objective health risk factors were also measured. Comparisons between responses were undertaken using kappa and correlation statistics to determine levels of agreement. Results The levels of agreement between online versus F2F responses for the seven compulsory Stage 1 questions (known diseases and signs and/or symptoms of disease) were >94% (kappa = 0.644-0.794). Response comparisons for Stage 2 questions on health risk factors were also generally high (>82% agreement) but there were larger differences between reported and measured risk factors in Stage 3. Conclusions Levels of agreement between the Stage 1 responses were substantial and support the use of this online option for pre-exercise screening. There were larger differences between self-reported and objectively measured health risk factors in Stages 2 and 3.